Ultrasound-guided serratus anterior plane block versus thoracic paravertebral block for perioperative analgesia in thoracotomy - Saad, Fady Samy (Saudi J Anaesth, 2018)
BACKGROUND: Thoracotomy needs adequate powerful postoperative analgesia. This study aims to compare the safety and efficacy of ultrasound (US)-guided serratus anterior plane block (SAPB) and thoracic paravertebral block (TPVB) for perioperative analgesia in cancer patients having lung lobectomy. PATIENTS AND METHODS: This clinical trial involved 90 patients with lung cancer scheduled for lung lobectomy randomly divided into three groups according to the type of preemptive regional block. Group TPVB received US-guided TPVB. In Group SAPB, US-guided SAPB was performed. The patients of the control Group received general anesthesia alone. The outcome measures were postoperative visual analog scale (VAS) score, intraoperative fentanyl consumption, time of first rescue analgesic, total dose postoperative analgesic, and drug-related adverse effects. RESULTS: Analgesia was adequate in TPVB and SAPB groups up to 24 h. VAS score was comparable in TPVB and SAPB groups and significantly lower compared to control group up to 9 h postoperatively. At 12 and 24 h, TPVB group had significantly lower VAS score relative to SAPB and control groups. Total intraoperative fentanyl consumption was significantly lower in TPVB and SAPB Groups compared to control group. The majority of TPVB Group cases did not need rescue morphine, while the majority of control group needed two doses (P < 0.001). The hemodynamic variables were stable in all patients. Few cases reported trivial adverse effects. CONCLUSION: Preemptive TPVB and SAPB provide comparable levels of adequate analgesia for the first 24 h after thoracotomy. TPVB provided better analgesia after 12 h. The two procedures reduce intraoperative fentanyl and postoperative morphine consumption.